THE IMPORTANCE OF EDUCATION METHODS IN THE FORMATION OF THE CHILD’S PERSONALITY IN THE FAMILY - Boronova Khilola Akramjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
Education is a practical pedagogical process aimed at forming certain physical, mental, moral and spiritual qualities in a person; It is a set of measures taken to ensure that a person has the characteristics necessary for living in society, and some methods of forming a perfect human personality in the family through the means of education are highlighted.